Antibodies against carbamylated vimentin exist in systemic lupus erythematosus and correlate with disease activity. (March 2020) - Li, Y; Jia, R; Liu, Y; Tang, S; Ma, X; Shi, L; Zhao, J; Hu, F; Li, Z
Objectives: Antibodies against carbamylated protein (anti-CarP) were found to be a promising marker to evaluate joint damage and disease activity in patients with rheumatoid arthritis (RA). However, whether anti-CarP antibodies were present in systemic lupus erythematosus (SLE) remained ambiguous. We have therefore undertaken this study to assess the levels of serum anti-CarP antibodies and to evaluate their clinical value in SLE. Methods: Serum levels of antibodies against carbamylated-vimentin (anti-Carp) were measured by enzyme immunosorbent assay in 100 patients with SLE, 76 with RA, 17 with primary Sjögren syndrome (pSS), and 68 healthy controls. Data analyses between anti-Carp antibodies and other laboratory measures were performed using SPSS 24 software for Windows. Results: The levels of serum anti-CarP antibodies in patients with SLE were significantly higher than those in healthy controls. In addition, anti-CarP antibodies were present in SLE patients lacking the disease-specific antibodies, including anti-Smith–negative patients (24.4%, 21/86), anti-dsDNA–negative patients (29.3%, 12/41), anti-nucleosome–negative patients (21.4%, 9/42), and antiribosomal P protein antibody–negative patients (23.7%, 18/76). There were significant differences between the anti-CarP–positive and anti-CarP–negative SLE patients in clinical and laboratory features, such as age, erythrocyte sedimentation rate (ESR), C-reactive protein, rheumatoid factor, third-generation cyclic citrullinated peptide (CCP3), anticardiolipin, D-dipolymer, complement 3, immunoglobulin G (IgG), red blood cell count (RBC) and hemoglobin. After adjusting for age and disease duration, the high levels of anti-CarP antibodies were still correlated with low RBC, hemoglobin and high ESR, IgG and CCP3. Active SLE patients demonstrated higher anti-CarP IgG than inactive patients. Moreover, the levels of anti-CarP were significantly higher in SLE patients with arthralgia and/or arthritis than in those without joint involvement. Conclusions: Anti-CarP antibodies were present in SLE patients and associated with the disease severity. These might provide a potential supplement to other specific autoantibodies for diagnosis of SLE and serve as a promising marker for measuring joint damage in the disease.